Method for manufacturing single-layer phase difference material
By using a polymer composition with a photoreactive site and controlling the wavelength ratio of polarized ultraviolet rays, the problem of insufficient exposure energy of ultraviolet light in the prior art is solved, and the manufacturing of a single-layer phase difference material with high phase difference and birefringence is achieved.
Patent Information
- Application Number
- CN202180066988.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-30
- Filing Date
- 2021-09-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-09-29
AI Technical Summary
In the prior art, when manufacturing liquid crystal alignment films and phase difference materials, the absorption peak of short-wavelength ultraviolet light is too large, resulting in insufficient exposure energy and insufficient phase difference and birefringence amount.
A polymer composition containing a photoreactive site with a wavelength of 365 nm for photodimerization or photoisomerization is used to produce a single-layer phase difference material by irradiating polarized light with a ratio of 313 nm to less than 10% of the total amount of light at a wavelength of 313 nm and light at a wavelength of 365 nm.
The manufacturing of a single-layer phase difference material with high phase difference value and birefringence is achieved, the problem of insufficient exposure energy is solved, and optical anisotropy is improved.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a single-layer phase difference material, and more specifically, to a material having optical properties suitable for use in display devices or recording materials, and in particular to a method for producing a single-layer phase difference material that can be suitable for use in optical compensation films such as polarizing plates and phase difference plates for organic electroluminescence (EL) display devices or liquid crystal displays. Background Art
[0002] Due to the requirements of improving the display quality and lightening of organic EL display devices and liquid crystal display devices, the requirements for polymer films with controlled internal molecular orientation structures as optical compensation films such as polarizing plates and phase difference plates are increasing. In order to meet this requirement, films using the optical anisotropy of polymerizable liquid crystal compounds have been developed. The polymerizable liquid crystal compound used here is usually a liquid crystal compound having a polymerizable group and a liquid crystal structure part (a structure part having a spacer part and a liquid crystal base part), and acrylic groups are widely used as the polymerizable group.
[0003] Such polymerizable liquid crystal compounds are usually polymerized by irradiation with radiation such as ultraviolet rays to form polymers (films). For example, it is known that: a specific polymerizable liquid crystal compound having an acrylic group is loaded between supports, and the compound is kept in a liquid crystal state while being irradiated with radiation to obtain a polymer (Patent Document 1); a photopolymerization initiator is added to a mixture of two polymerizable liquid crystal compounds having acrylic groups or a composition in which a chiral liquid crystal is mixed in the mixture, and ultraviolet rays are irradiated to obtain a polymer (Patent Document 2).
[0004] In addition, various single-layer coating type alignment films have been reported, such as alignment films using polymerizable liquid crystal compounds or polymers (Patent Documents 3 and 4) and alignment films using polymers containing photo-crosslinking sites (Patent Documents 5 and 6), which do not require a liquid crystal alignment film.
[0005] In the past, when manufacturing liquid crystal alignment films and phase difference materials, the wavelength of radiation such as ultraviolet rays required for formation varies depending on the structure of the organic compound. Therefore, in order to maximize the optical anisotropy, the exposure treatment is performed at a wavelength in the region where the absorption peak of ultraviolet light originating from the structure of the organic compound is the largest. At this time, when using a compound having a maximum absorption peak of ultraviolet light in the short wavelength region (250 to 320 nm), depending on the film thickness, the short wavelength light cannot impart sufficient exposure energy to the film, and there is a problem that the phase difference and birefringence amount become insufficient.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 62-70407
[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 9-208957
[0010] Patent Document 3: European Patent Application Publication No. 1090325
[0011] Patent Document 4: International Publication No. 2008 / 031243
[0012] Patent Document 5: Japanese Patent Application Publication No. 2008-164925
[0013] Patent Document 6: Japanese Patent Application Laid-Open No. 11-189665 Summary of the invention
[0014] Technical problem to be solved by the invention
[0015] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a method for producing a single-layer retardation material, wherein the method can produce a single-layer retardation material having a high retardation value and a high birefringence.
[0016] Means for solving technical problems
[0017] In order to solve the above-mentioned technical problems, the present inventors have repeatedly conducted in-depth studies from the viewpoint of the wavelength of polarized ultraviolet rays, and as a result, they have found that when a single-layer phase difference material is prepared using a composition comprising a polymer having a photoreactive portion that undergoes photodimerization or photoisomerization with light of a wavelength of 365 nm, by irradiating polarized ultraviolet rays in which the amount of light with a wavelength of 313 nm in the total amount of light with a wavelength of 365 nm and light with a wavelength of 313 nm is controlled to be less than a specified amount, that is, by irradiating polarized ultraviolet rays in which the proportion of light with a wavelength of 365 nm is greater than that of light with a wavelength of 313 nm that is conventionally used in liquid crystal alignment films, a single-layer phase difference material having a high phase difference value and refractive index anisotropy (Δn) can be obtained, thereby completing the present invention.
[0018] That is, the present invention provides the following.
[0019] 1. A method for manufacturing a single-layer phase difference material, characterized in that it comprises the following steps:
[0020] (I) coating the polymer composition on a substrate and drying it to form a coating film; and
[0021] (II) irradiating the coating film with polarized ultraviolet light,
[0022] The polymer composition comprises a polymer having a photoreactive site in a side chain that undergoes photodimerization or photoisomerization with light of a wavelength of 365 nm,
[0023] The amount of the light with a wavelength of 313 nm in the polarized ultraviolet light accounts for 10% or less of the total amount of the light with a wavelength of 365 nm and the light with a wavelength of 313 nm.
[0024] 2. The method for producing a single-layer phase difference material according to 1, wherein the amount of light having a wavelength of 313 nm in the total amount of the light having a wavelength of 365 nm and the light having a wavelength of 313 nm is 5% or less.
[0025] 3. The method for producing a single-layer phase difference material according to 1 or 2, wherein the polarized ultraviolet light does not include light with a wavelength of 313 nm.
[0026] 4. The method for producing a single-layer phase difference material according to any one of 1 to 3, comprising the following steps:
[0027] (III) Heating the coating film irradiated with the polarized ultraviolet rays.
[0028] 5. The method for producing a single-layer retardation material according to any one of 1 to 3, wherein the coating film irradiated with polarized ultraviolet light has a thickness of 0.5 μm or more.
[0029] 6. The method for producing a single-layer retardation material according to any one of 1 to 5, wherein the polymer has a side chain, and the side chain has any photoreactive site represented by the following formulae (a1) to (a3).
[0030] [Chemistry 1]
[0031]
[0032] (In the formula, A 1 , A 2 and D each independently represent a single bond, -O-, -CH2-, -COO-, -OCO-, -CONH- or -NH-CO-,
[0033] L represents an alkylene group having 1 to 12 carbon atoms, wherein the hydrogen atoms of the alkylene group may be independently replaced by halogen atoms,
[0034] T represents a single bond or an alkylene group having 1 to 12 carbon atoms, the hydrogen atoms of which may be replaced by halogen atoms,
[0035] When T is a single bond, A 2 It also represents a single bond.
[0036] Y 1 represents a divalent benzene ring,
[0037] P 1 , Q 1 and Q 2 each independently represents a group selected from the group consisting of a benzene ring and an alicyclic hydrocarbon ring having 5 to 8 carbon atoms,
[0038] R represents a hydrogen atom, a cyano group, a halogen atom, an alkyl group having 1 to 5 carbon atoms, an alkylcarbonyl group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 7 carbon atoms, or an alkyloxy group having 1 to 5 carbon atoms,
[0039] Y 1 , P 1 , Q 1 and Q 2 In the formula (a), the hydrogen atoms bonded to the benzene ring may be independently replaced by a cyano group, a halogen atom, an alkyl group having 1 to 5 carbon atoms, an alkylcarbonyl group having 1 to 5 carbon atoms, or an alkyloxy group having 1 to 5 carbon atoms.
[0040] X 1 and X 2 each independently represents a single bond, -O-, -COO- or -OCO-,
[0041] n1 and n2 are each independently 0, 1 or 2,
[0042] When X 1 When the number is 2, X 1 They can be the same or different; when X 2 When the number is 2, X 2 They can be the same or different from each other.
[0043] When Q 1 When the number is 2, Q 1 They can be the same or different; when Q 2 When the number is 2, Q 2 They can be the same or different, and the dotted line represents a bond.)
[0044] 7. The method for producing a single-layer phase difference material according to 6, wherein the polymer further has a side chain that does not show photo-alignment.
[0045] 8. The method for producing a single-layer retardation material according to 7, wherein the side chain that does not exhibit photo-alignment is any one side chain selected from the group consisting of the following formulae (1) to (12).
[0046] [Chemistry 2]
[0047]
[0048] [Chemistry 3]
[0049]
[0050] (In formulas (1) to (12), A 3 and A 4 each independently represents a single bond, -O-, -CH2-, -C(=O)-O-, -OC(=O)-, -C(=O)NH-, or -NHC(=O)-, R 11 represents -NO2, -CN, a halogen atom, a phenyl group, a naphthyl group, a biphenyl group, a furyl group, a monovalent nitrogen-containing heterocyclic group, a monovalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, an alkyl group having 1 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms, and R 12 represents a group selected from the group consisting of a phenyl group, a naphthyl group, a biphenyl group, a furyl group, a monovalent nitrogen-containing heterocyclic group, a monovalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, and a group obtained by combining these groups, wherein the hydrogen atom bonded to these groups may be replaced by -NO2, -CN, a halogen atom, an alkyl group having 1 to 5 carbon atoms, or an alkoxy group having 1 to 5 carbon atoms, and R 13 represents a hydrogen atom, -NO2, -CN, -CH=C(CN)2, -CH=CH-CN, a halogen atom, a phenyl group, a naphthyl group, a biphenyl group, a furyl group, a monovalent nitrogen-containing heterocyclic group, a monovalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, an alkyl group having 1 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms, E represents -C(=O)O- or -OC(=O)-, d represents an integer of 1 to 12, k1 to k5 are each independently an integer of 0 to 2, the total of k1 to k5 is 2 or more, k6 and k7 are each independently an integer of 0 to 2, the total of k6 and k7 is 1 or more, m1, m2 and m3 are each independently an integer of 1 to 3, n is 0 or 1, Z 1 and Z 2 Each independently represents a single bond, -C(=O)-, -CH2O- or -CF2-, and the dotted line represents a bond.)
[0051] 9. The method for producing a single-layer phase difference material according to any one of 6 to 8, wherein the side chain having a photoreactive site is any group represented by the following formulae (a1-1) to (a3-1):
[0052] [Chemistry 4]
[0053]
[0054] (In the formula, A 2 , L, T, Y 1 , P 1 , Q 1 , R and dotted line have the same meanings as above. ).
[0055] Effects of the Invention
[0056] According to the manufacturing method of the present invention, a single-layer phase difference material with high phase difference value and birefringence can be obtained even if polarized ultraviolet light with a wavelength of 365 nm, which is generally not used in the exposure treatment of organic compounds having photoreactive groups, is used in which the proportion of light with a wavelength of 313 nm is greater than that of light with a wavelength of 365 nm. DETAILED DESCRIPTION
[0057] Hereinafter, the present invention will be described in detail.
[0058] The method for producing a single-layer phase difference material of the present invention is characterized in that it includes the following steps: (I) applying a polymer composition on a substrate and drying it to form a coating film; and (II) irradiating the obtained coating film with polarized ultraviolet light, wherein the polymer composition includes a polymer having a photoreactive site that undergoes photodimerization or photoisomerization with light of a wavelength of 365 nm, and the amount of light with a wavelength of 313 nm in the polarized ultraviolet light accounts for less than 10% of the total amount of light with a wavelength of 365 nm and light with a wavelength of 313 nm.
[0059] [Step (I)]
[0060] Step (I) is a step of applying a polymer composition to a substrate to form a coating. More specifically, on a substrate (e.g., a silicon / silicon dioxide coated substrate, a silicon nitride substrate, a metal-coated substrate (e.g., aluminum, molybdenum, chromium, etc.), a glass substrate, a quartz substrate, an ITO substrate, etc.), a film (e.g., a triacetylcellulose (TAC) film, a cycloolefin polymer film, a polyethylene terephthalate film, an acrylic film, etc.), the polymer composition is applied by methods such as rod coating, spin coating, flow coating, roller coating, slit coating, slit coating followed by spin coating, inkjet method, and printing method. After coating, it is dried naturally, or heated by a heating unit such as a hot plate, a heat circulation oven, an IR (infrared) oven, etc., so that the solvent evaporates and a coating can be obtained. When heating is performed by a heating unit, the temperature is not particularly limited, and is preferably 50 to 200° C., and more preferably 50 to 150° C.
[0061] The polymer composition used in the present invention comprises a side chain polymer that can show liquid crystallinity, or a mixed side chain polymer (hereinafter, also referred to as a side chain polymer) having a liquid crystal side chain polymer and a photosensitive side chain polymer, respectively, and the obtained coating is also a film having a side chain polymer containing liquid crystallinity and photosensitivity. The coating is not subjected to friction treatment, but is oriented by polarized light irradiation. Moreover, after polarized light irradiation, the process of heating the side chain polymer film becomes a film (hereinafter, also referred to as a single-layer phase difference material) endowed with optical anisotropy. At this time, the tiny anisotropy exhibited by polarized light irradiation becomes a driving force, and the side chain polymer itself is effectively reoriented by self-organization. As a result, as a single-layer phase difference material, efficient orientation treatment can be achieved, and a single-layer phase difference material endowed with high optical anisotropy can be obtained.
[0062] As the side chain polymer, a polymer having a photoreactive site that undergoes photodimerization or photoisomerization with light of a wavelength of 365 nm is used.
[0063] As a polymer, there is no particular limitation as long as it is a side chain polymer having the above-mentioned properties. Preferably, it is a polymer having a side chain having any photoreactive site represented by the following formulas (a1) to (a3) (hereinafter also referred to as side chain a), and more preferably a polymer having a side chain having any photoreactive site represented by the following formulas (a1-1) to (a3-1).
[0064] From the viewpoint of solubility in a solvent, the number of benzene rings in the side chain having one photoreactive site is preferably 3 or less.
[0065] [Chemistry 5]
[0066]
[0067] (In the formula, the dotted line represents the bonding bond.)
[0068] [Chemistry 6]
[0069]
[0070] (In the formula, the dotted line represents the bonding bond.)
[0071] In the above formulas, A 1 , A 2 and D each independently represent a single bond, -O-, -CH2-, -COO-, -OCO-, -CONH-, or -NH-CO-.
[0072] L represents an alkylene group having 1 to 12 carbon atoms, and the hydrogen atoms of the alkylene group may be independently replaced by halogen atoms.
[0073] T represents a single bond or an alkylene group having 1 to 12 carbon atoms, and the hydrogen atoms of the alkylene group may be replaced by halogen atoms. 2 Also represents a single bond.
[0074] Y 1 It represents a divalent benzene ring.
[0075] P 1 , Q 1 and Q 2 Each independently represents a group selected from the group consisting of a benzene ring and an alicyclic hydrocarbon ring having 5 to 8 carbon atoms.
[0076] R represents a hydrogen atom, a cyano group, a halogen atom, an alkyl group having 1 to 5 carbon atoms, an alkylcarbonyl group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 7 carbon atoms, or an alkyloxy group having 1 to 5 carbon atoms.
[0077] In Y 1 , P 1 , Q 1 and Q 2 In the above, the hydrogen atoms bonded to the benzene ring may be independently replaced by a cyano group, a halogen atom, an alkyl group having 1 to 5 carbon atoms, an alkylcarbonyl group having 1 to 5 carbon atoms, or an alkyloxy group having 1 to 5 carbon atoms.
[0078] X 1 and X 2 Each independently represents a single bond, -O-, -COO- or -OCO-.
[0079] n1 and n2 are each independently 0, 1 or 2.
[0080] When X 1 When the number is 2, X 1 They can be the same or different; when X 2 When the number is 2, X 2 They can be the same or different; when Q 1 When the number is 2, Q 1 They can be the same or different; when Q 2 When the number is 2, Q 2 They can be the same or different from each other.
[0081] The alkylene group having 1 to 12 carbon atoms may be any of a linear, branched or cyclic group, and specific examples thereof include a methylene group, an ethylene group, a propane-1,3-diyl group, a butane-1,4-diyl group, a pentane-1,5-diyl group, a hexane-1,6-diyl group, a heptane-1,7-diyl group, an octane-1,8-diyl group, a nonane-1,9-diyl group, and a decane-1,10-diyl group.
[0082] Specific examples of the alicyclic hydrocarbon ring having 5 to 8 carbon atoms include a cyclopentane ring, a cyclohexane ring, a cycloheptane ring, and a cyclooctane ring.
[0083] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0084] The alkyl group having 1 to 5 carbon atoms may be linear or branched, and specific examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, and n-pentyl.
[0085] Specific examples of the alkylcarbonyl group having 1 to 5 carbon atoms include methylcarbonyl (acetyl), ethylcarbonyl, n-propylcarbonyl, n-butylcarbonyl, and n-pentylcarbonyl.
[0086] Specific examples of the cycloalkyl group having 3 to 7 carbon atoms include cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl.
[0087] Specific examples of the alkyloxy group having 1 to 5 carbon atoms include a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, and an n-pentyloxy group.
[0088] In particular, as the polymer, a polymer having a side chain having a photoreactive site represented by any one of the following formulae (a1-1-1) to (a3-1-1) is more preferred.
[0089] [Chemistry 7]
[0090]
[0091] (In the formula, L, Q 1 , A 2 , T and R have the same meanings as above.)
[0092] The side chain polymer used in the present invention has a photosensitive side chain bonded to the main chain, which can sense light of a wavelength of 365nm and produce a crosslinking reaction or an isomerization reaction. The structure of the photosensitive side chain polymer is not particularly limited as long as it satisfies such characteristics, but it is preferred that the side chain structure has a rigid liquid crystal unit component. When the above-mentioned side chain polymer is made into a single-layer phase difference material, stable optical anisotropy can be obtained.
[0093] As a more specific example of the structure of a photosensitive side chain polymer, a structure having a main chain and a side chain a consisting of at least one selected from the group consisting of free radical polymerizable groups such as (meth)acrylate, itaconate, fumarate, maleate, α-methylene-γ-butyrolactone, styrene, vinyl, maleimide, norbornene and siloxane is preferred.
[0094] The side chain type polymer may further have a side chain that does not exhibit photo-alignment properties (hereinafter, also referred to as a side chain b).
[0095] Such a side chain b is preferably any one selected from the group consisting of the following formulae (1) to (12), but is not limited thereto.
[0096] [Chemistry 8]
[0097]
[0098] (Dashed lines represent bonds.)
[0099] [Chemistry 9]
[0100]
[0101] (Dashed lines represent bonds.)
[0102] In formulas (1) to (12), A 3 and A 4 each independently represents a single bond, -O-, -CH2-, -C(=O)-O-, -OC(=O)-, -C(=O)NH-, or -NHC(=O)-, R 11 represents -NO2, -CN, a halogen atom, a phenyl group, a naphthyl group, a biphenyl group, a furyl group, a monovalent nitrogen-containing heterocyclic group, a monovalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, an alkyl group having 1 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms, and R 12 represents a group selected from the group consisting of a phenyl group, a naphthyl group, a biphenyl group, a furyl group, a monovalent nitrogen-containing heterocyclic group, a monovalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, and a group obtained by combining these groups, wherein the hydrogen atom bonded to these groups may be replaced by -NO2, -CN, a halogen atom, an alkyl group having 1 to 5 carbon atoms, or an alkoxy group having 1 to 5 carbon atoms, and R 13 represents a hydrogen atom, -NO2, -CN, -CH=C(CN)2, -CH=CH-CN, a halogen atom, a phenyl group, a naphthyl group, a biphenyl group, a furyl group, a monovalent nitrogen-containing heterocyclic group, a monovalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, an alkyl group having 1 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms, E represents -C(=O)O- or -OC(=O)-, d represents an integer of 1 to 12, k1 to k5 are each independently an integer of 0 to 2, the total of k1 to k5 is 2 or more, k6 and k7 are each independently an integer of 0 to 2, the total of k6 and k7 is 1 or more, m1, m2 and m3 are each independently an integer of 1 to 3, n is 0 or 1, Z 1 and Z 2 Each independently represents a single bond, -C(=O)-, -CH2O-, or -CF2-. The dotted line represents a bond.
[0103] Specific examples of the monovalent nitrogen-containing heterocyclic group include pyrrolidinyl, piperidinyl, piperazinyl, pyrrolyl, pyridyl and the like. Specific examples of the monovalent alicyclic hydrocarbon group having 5 to 8 carbon atoms include cyclopentyl, cyclohexyl and the like.
[0104] In addition, examples of the alkyl group and the alkoxy group include 5 The same groups as exemplified in .
[0105] Among these, as the side chain b, a side chain represented by any one of the formulae (1) to (11) is preferred.
[0106] The side chain type polymer used in the present invention can be obtained by polymerizing a monomer having a structure represented by any one of formulae (a1) to (a3) and, if necessary, a monomer that provides a side chain b.
[0107] Examples of the monomer having a structure represented by any one of formulae (a1) to (a3) (hereinafter also referred to as monomer M1) include compounds represented by the following formulae (M1-1) to (M1-3).
[0108] [Chemistry 10]
[0109]
[0110] (In the formula, A 1 , A 2 , D, L, T, Y 1 , P 1 , Q 1 , Q 2 , R, X 1 , X 2 , n1 and n2 have the same meanings as above. )
[0111] As the monomer M1, any of the compounds represented by the following formulae (M1-1-1) to (M1-3-1) is preferred.
[0112] [Chemistry 11]
[0113]
[0114] (In the formula, A 2 , L, T, Y 1 , P 1 , Q 1 and R have the same meanings as above.)
[0115] In particular, any compound represented by the following formulae (M1-1-1-1) to (M1-3-1-1) is more preferred.
[0116] [Chemistry 12]
[0117]
[0118] (In the formula, L, Q 1 , A 2 , T and R have the same meanings as above.)
[0119] In the above formulae, PG is a polymerizable group, preferably a group selected from the groups represented by the following formulae PG1 to PG8. In particular, from the viewpoint of easy control of the polymerization reaction and the stability of the polymer, an acrylic group or a methacrylic group represented by PG1 is preferred.
[0120] [Chemistry 13]
[0121]
[0122] (Where M 1 represents a hydrogen atom or a methyl group, and the dotted line represents the bond with L. )
[0123] Examples of the monomer (M1-1) include monomers selected from the following formulae A-1-1 to A-1-12. In the following formulae A1-1 to A1-12, PG represents any polymerizable group selected from the groups represented by the above formulae PG1 to PG8, and s1 represents the number of methylene groups, which is an integer of 2 to 9.
[0124] [Chemistry 14]
[0125]
[0126] [Chemistry 15]
[0127]
[0128] [Chemistry 16]
[0129]
[0130] Examples of the monomer (M1-2) include monomers selected from the following formulae A-2-1 to A-2-8. In the following formulae A2-1 to A2-8, PG represents a polymerizable group selected from the groups represented by the above formulae PG1 to PG8, and s1 and s2 each independently represent the number of methylene groups, which is an integer of 2 to 9.
[0131] [Chemistry 17]
[0132]
[0133] [Chemistry 18]
[0134]
[0135] Some of the above monomers are commercially available, and some can be produced by the method described in, for example, International Publication No. 2014 / 074785.
[0136] Examples of the monomer (M1-3) include monomers selected from the following formulae A-3-1 to A-3-3. In the following formulae, PG represents a polymerizable group selected from the groups represented by the above formulae PG1 to PG8, and s1 represents the number of methylene groups, which is an integer of 2 to 9.
[0137] [Chemistry 19]
[0138]
[0139] Specific examples of the above-mentioned monomer (M1-3) include 4-(6-methacryloyloxyhexyl-1-oxy)cinnamic acid, 4-(6-acryloyloxyhexyl-1-oxy)cinnamic acid, 4-(3-methacryloyloxypropyl-1-oxy)cinnamic acid, and 4-(4-(6-methacryloyloxyhexyl-1-oxy)benzoyloxy)cinnamic acid.
[0140] The monomer that imparts the side chain b that does not exhibit photo-alignment properties (hereinafter, also referred to as monomer M2) is a monomer that can form a mesogen group at the side chain site.
[0141] The mesogen group as a side chain may be a group that forms a mesogen structure independently, such as biphenyl or phenyl benzoate, or a group that forms a mesogen structure by hydrogen bonding such as benzoic acid. The following structure is preferred as a mesogen group as a side chain.
[0142] [Chemistry 20]
[0143]
[0144] As a more specific example of the monomer M2, the following structure is preferred, wherein the structure has at least one polymerizable group selected from the group consisting of free radical polymerizable groups such as hydrocarbons, (meth)acrylates, itaconates, fumarates, maleates, α-methylene-γ-butyrolactone, styrene, vinyl, maleimide, norbornene, and siloxane, and a structure comprising at least one of formulae (1) to (12). In particular, the monomer M2 is preferably a monomer having a (meth)acrylate as a polymerizable group, and preferably a monomer having -COOH at the end of the side chain.
[0145] Preferred examples of the monomer M2 include monomers represented by the following formulae (M2-1) to (M2-9).
[0146] [Chemistry 21]
[0147]
[0148] (In the formula, PG and s1 have the same meanings as above.)
[0149] [Chemistry 22]
[0150]
[0151] (In the formula, PG and s1 have the same meanings as above.)
[0152] In addition, other monomers can be copolymerized within the range that does not impair the performance of photoreactivity and / or liquid crystal properties. As other monomers, for example, monomers that can undergo free radical polymerization reaction and are available industrially can be cited. Specific examples of other monomers include unsaturated carboxylic acids, acrylate compounds, methacrylate compounds, maleimide compounds, acrylonitrile, maleic anhydride, styrene compounds, vinyl compounds, etc.
[0153] Specific examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, itaconic acid, maleic acid, and fumaric acid.
[0154] Specific examples of the acrylate compound include methyl acrylate, ethyl acrylate, isopropyl acrylate, benzyl acrylate, naphthyl acrylate, anthracene acrylate, anthracene methyl acrylate, phenyl acrylate, 2,2,2-trifluoroethyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, isobornyl acrylate, 2-methoxyethyl acrylate, methoxytriethylene glycol acrylate, 2-ethoxyethyl acrylate, tetrahydrofurfuryl acrylate, 3-methoxybutyl acrylate, 2-methyl-2-adamantyl acrylate, 2-propyl-2-adamantyl acrylate, 8-methyl-8-tricyclodecanyl acrylate, and 8-ethyl-8-tricyclodecanyl acrylate.
[0155] Specific examples of the methacrylate compound include methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, benzyl methacrylate, naphthyl methacrylate, anthracene methacrylate, anthracene methyl methacrylate, phenyl methacrylate, 2,2,2-trifluoroethyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, 2-methoxyethyl methacrylate, methoxytriethylene glycol methacrylate, 2-ethoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, 3-methoxybutyl methacrylate, 2-methyl-2-adamantyl methacrylate, 2-propyl-2-adamantyl methacrylate, 8-methyl-8-tricyclodecanyl methacrylate, and 8-ethyl-8-tricyclodecanyl methacrylate.
[0156] Specific examples of the vinyl compound include vinyl ether, methyl vinyl ether, benzyl vinyl ether, 2-hydroxyethyl vinyl ether, phenyl vinyl ether, propyl vinyl ether, and the like.
[0157] Specific examples of the styrene compound include styrene, 4-methylstyrene, 4-chlorostyrene, 4-bromostyrene, and the like.
[0158] Specific examples of the maleimide compound include maleimide, N-methylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide.
[0159] In the side chain polymer, the content of the side chain a and the side chain b is not particularly limited, but from the viewpoint of photoreactivity, the side chain a is preferably 5 to 99.9 mol%, more preferably 10 to 95 mol%. From the viewpoint of photoreactivity, the side chain b is preferably 95 mol% or less.
[0160] The side chain type polymer used in the present invention may contain other side chains. When the total content of the side chain a and the side chain b is less than 100 mol %, the content of the other side chains is the remainder.
[0161] The manufacturing method of the above-mentioned side chain type polymer is not particularly limited, and a general method for industrial processing can be utilized. Specifically, it can be manufactured by free radical polymerization, cationic polymerization or anionic polymerization using the vinyl groups of the above-mentioned monomer M1, the monomer M2 as required, and other monomers. Among them, free radical polymerization is particularly preferred from the viewpoints of the ease of reaction control, etc.
[0162] As the polymerization initiator for radical polymerization, known compounds such as radical polymerization initiators (radical thermal polymerization initiators, radical photopolymerization initiators) and reversible addition-fragmentation chain transfer (RAFT) polymerization agents can be used.
[0163] The free radical thermal polymerization initiator is a compound that generates free radicals by heating to a temperature above the decomposition temperature. As such free radical thermal polymerization initiators, for example, ketone peroxides (methyl ethyl ketone peroxide, cyclohexanone peroxide, etc.), diacyl peroxides (acetyl peroxide, benzoyl peroxide, etc.), hydroperoxides (hydrogen peroxide, tert-butyl hydroperoxide, cumyl hydroperoxide, etc.), dialkyl peroxides (di-tert-butyl peroxide, dicumyl peroxide, dilauroyl peroxide, etc.), peroxyketals (dibutyl peroxycyclohexane, etc.), alkyl peresters (tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, tert-amyl peroxy 2-ethylcyclohexane acid, etc.), persulfates (potassium persulfate, sodium persulfate, ammonium persulfate, etc.), azo compounds (azobisisobutyronitrile, 2,2'-bis(2-hydroxyethyl)azobisisobutyronitrile, etc.), etc. The free radical thermal polymerization initiator can be used alone or in combination of two or more.
[0164] The free radical photopolymerization initiator is not particularly limited as long as it is a compound that initiates free radical polymerization by light irradiation. As such free radical photopolymerization initiators, there are exemplified: benzophenone, Michler's ketone, 4,4'-bis(diethylamino)benzophenone, xanthone, thioxanthone, isopropylxanthone, 2,4-diethylthioxanthone, 2-ethylanthraquinone, acetophenone, 2-hydroxy-2-methylpropiophenone, 2-hydroxy-2-methyl-4'-isopropylpropiophenone, 1-hydroxycyclohexylphenyl ketone, isopropylbenzoin ether, isobutylbenzoin ether, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, camphorquinone, benzanthrone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinylphenyl)-1-propanone, )-Butanone-1, 4-dimethylaminobenzoic acid ethyl ester, 4-dimethylaminobenzoic acid isopentyl ester, 4,4'-di(tert-butylperoxycarbonyl)benzophenone, 3,4,4'-tri(tert-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2-(4'-methoxyphenylvinyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxyphenylvinyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2',4'-dimethoxyphenylvinyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2'-methoxyphenylvinyl)-4,6-bis(trichloromethyl)-s-triazine, s-triazine, 1,3-bis(trichloromethyl)-5-(2'-chlorophenyl)-s-triazine, 1,3-bis(trichloromethyl)-5-(4'-methoxyphenyl)-s-triazine, 2-(p-dimethylaminophenyl)benzoxazole, 2-(p-dimethylaminophenyl)benzothiazole, 2-mercaptobenzothiazole, 3,3'-carbonylbis(7-diethylaminocoumarin), 2-(o-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2-chlorophenyl)-4,4',5 ,5'-tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2,4-dichlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4-dibromophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4,6-trichlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 3-(2-methyl-2-dimethylaminopropionyl)carbazole, 3,6-bis(2-methyl-2-morpholinopropionyl)-9-n-dodecylcarbazole, 1-hydroxycyclohexyl phenyl ketone, bis(5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, 3,3',4,4'-tetra(tert-hexylperoxycarbonyl)benzophenone, 3,3'-di(methoxycarbonyl)-4,4'-di(tert-butylperoxycarbonyl)benzophenone, 3,4'-di(methoxycarbonyl)-4,3'-di(tert-butylperoxycarbonyl)benzophenone, 4,4'-di(methoxycarbonyl)-3,3'-di(tert-butylperoxycarbonyl)benzophenone, 2-(3-methyl-3H-benzothiazol-2-ylidene)-1-naphth-2-yl-ethanone, 2-(3-methyl-1,3-benzothiazol-2(3H)-ylidene)-1-(2-benzoyl)ethanone, etc. The free radical photopolymerization initiator may be used alone or in combination of two or more.
[0165] The radical polymerization method is not particularly limited, and emulsion polymerization, suspension polymerization, dispersion polymerization, precipitation polymerization, bulk polymerization, solution polymerization, and the like can be used.
[0166] The organic solvent used in the polymerization reaction is not particularly limited as long as it is an organic solvent that dissolves the generated polymer. Specific examples thereof include: N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-methyl-ε-caprolactam, dimethyl sulfoxide, tetramethylurea, pyridine, dimethyl sulfone, hexamethylphosphoramide, γ-butyrolactone, isopropyl alcohol, methoxymethylpentanol, dipentene, ethylpentyl ketone, methyl nonyl ketone, methyl ethyl ketone, methyl isopentyl ketone, methyl isopropyl ketone, methyl cellosolve, ethyl cellosolve, methyl cellosolve. Cellosolve acetate, ethyl cellosolve acetate, butyl carbitol, ethyl carbitol, ethylene glycol, ethylene glycol monoacetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, propylene glycol, propylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol tert-butyl ether, dipropylene glycol monomethyl ether, diethylene glycol, diethylene glycol monoacetate, diethylene glycol dimethyl ether, dipropylene glycol monoacetate monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monoacetate monoethyl ether, dipropylene glycol monopropyl ether , dipropylene glycol monoacetate monopropyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, 3-methyl-3-methoxybutanol, diisopropyl ether, ethyl isobutyl ether, diisobutylene, amyl acetate, butyl butyrate, butyl ether, diisobutyl ketone, methyl cyclohexene, propyl ether, dihexyl ether, 1,4-dioxane, n-hexane, n-pentane, n-octane, ethyl ether, cyclohexanone, ethylene carbonate, propylene carbonate, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, ethyl 3-methoxypropionic acid propyl ester, 3-methoxypropionic acid butyl ester, diethylene glycol dimethyl ether, 4-hydroxy-4-methyl-2-pentanone, 3-methoxy-N,N-dimethylpropionamide, 3-ethoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, etc. These organic solvents may be used alone or in combination of two or more.
[0167] Furthermore, even a solvent that does not dissolve the produced polymer may be used by mixing with the above-mentioned organic solvent as long as the produced polymer does not precipitate.
[0168] In addition, in radical polymerization, since oxygen in the organic solvent becomes a factor that inhibits the polymerization reaction, it is preferable to use an organic solvent that is degassed as much as possible.
[0169] The polymerization temperature during free radical polymerization can be selected from any temperature of 30 to 150° C., preferably in the range of 50 to 100° C. In addition, the reaction can be carried out at any concentration. If the concentration is too low, it is difficult to obtain a high molecular weight polymer. If the concentration is too high, the viscosity of the reaction solution becomes too high, and uniform stirring becomes difficult. Therefore, the monomer concentration is preferably 1 to 50% by mass, more preferably 5 to 30% by mass. The reaction can be carried out at a high concentration at the beginning, and then an organic solvent can be added.
[0170] In the above-mentioned free radical polymerization reaction, if the ratio of the free radical polymerization initiator is large relative to the monomer, the molecular weight of the obtained polymer becomes small, and if the ratio of the free radical polymerization initiator is small relative to the monomer, the molecular weight of the obtained polymer becomes large, so the ratio of the free radical initiator is preferably 0.1 to 20 mol% relative to the monomer to be polymerized. In addition, various monomer components, solvents, initiators, etc. can also be added during polymerization.
[0171] For the polymer generated by the reaction solution obtained by the above reaction, the reaction solution can be put into a poor solvent and precipitated and recovered, but the reprecipitation treatment is not necessary. As the poor solvent used in the precipitation, methanol, acetone, hexane, heptane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, benzene, ether, methyl ethyl ether, water, etc. can be mentioned. The polymer put into the poor solvent and precipitated can be filtered and recovered, and then dried at room temperature or heated under normal pressure or reduced pressure. In addition, if the operation of redissolving the recovered polymer in an organic solvent and reprecipitating and recovering is repeated 2 to 10 times, the impurities in the polymer can be reduced. As the poor solvent at this time, for example, alcohols, ketones, hydrocarbons, etc. can be mentioned. If more than 3 poor solvents selected from them are used, the efficiency of purification is further improved, so it is preferred.
[0172] The side chain polymer used in the present invention preferably has a weight average molecular weight of 2,000 to 2,000,000, more preferably 2,000 to 1,000,000, and even more preferably 5,000 to 200,000 as measured by GPC (Gel Permeation Chromatography) in consideration of the strength of the resulting coating film, the workability during coating film formation, and the uniformity of the coating film.
[0173] The polymerizable composition used in the present invention contains the side chain type polymer as described above and an organic solvent (good solvent).
[0174] The organic solvent is not particularly limited as long as it is an organic solvent that dissolves the polymer component. Specific examples thereof include: N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-methyl-ε-caprolactam, 2-pyrrolidone, N-ethyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, dimethyl sulfoxide, tetramethyl urea, pyridine, dimethyl sulfone, hexamethyl sulfoxide, γ-butyrolactone, 3-methoxy-N,N-dimethylpropionamide, 3-ethoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, 1,3-dimethyl-2-imidazolidinone, ethyl amyl ketone, methyl nonyl ketone, methyl ethyl ketone, methyl isopentyl ketone, 1-Hydroxy-4-methyl-2-pentanone, propylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol tert-butyl ether, dipropylene glycol monomethyl ether, diethylene glycol, diethylene glycol monoacetate, diethylene glycol dimethyl ether, dipropylene glycol monoacetate monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monoacetate monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monoacetate monopropyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, tetrahydrofuran, tetrahydrofurfuryl alcohol, etc. These may be used alone or in combination of two or more.
[0175] In addition, the polymer composition may include components other than the side chain polymer and the organic solvent (good solvent). Examples thereof include solvents (poor solvents) or compounds that improve the uniformity of film thickness and surface smoothness when the polymer composition is applied, compounds that improve the adhesion of the phase difference material to the substrate, etc., but are not limited to these.
[0176] Specific examples of solvents (poor solvents) for improving uniformity of film thickness and surface smoothness include isopropyl alcohol, methoxymethylpentyl alcohol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, methyl cellosolve acetate, ethyl cellosolve acetate, butyl carbitol, ethyl carbitol, ethyl carbitol acetate, ethylene glycol, ethylene glycol monoacetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, propylene glycol, propylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol tert-butyl ether, Butyl ether, dipropylene glycol monomethyl ether, diethylene glycol, diethylene glycol monoacetate, diethylene glycol dimethyl ether, dipropylene glycol monoacetate monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monoacetate monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monoacetate monopropyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, 3-methyl-3-methoxybutanol, diisopropyl ether, ethyl isobutyl ether, diisobutylene, amylene 1-Hexane, 1-pentane, 1-octane, ethyl ether, methyl lactate, ethyl lactate, propyl lactate, butyl lactate, isopentyl lactate, methyl acetate, ethyl acetate, butyl acetate, propylene glycol monoethyl acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, ethyl 3-ethoxypropionate Solvents having low surface tension, such as propionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 1-butoxy-2-propanol, 1-phenoxy-2-propanol, propylene glycol monoacetate, propylene glycol diacetate, propylene glycol-1-monomethyl ether-2-acetate, propylene glycol-1-monoethyl ether-2-acetate, dipropylene glycol, and 2-(2-ethoxypropoxy)propanol.
[0177] These poor solvents may be used alone or in combination of two or more.
[0178] When a poor solvent is used, the content thereof is preferably 5 to 80% by mass, more preferably 20 to 60% by mass in the solvent so as not to significantly reduce the solubility of the polymer.
[0179] As compounds for improving film thickness uniformity and surface smoothness, fluorine-based surfactants, silicone-based surfactants, nonionic surfactants, etc. can be cited. Specific examples thereof include: EFTOP (registered trademark) 301, EF303, EF352 (manufactured by Tohkem Products), MEGAFAC (registered trademark) F171, F173, F560, F563, R-30, R-40 (manufactured by DIC Corporation), Fluorad FC430, FC431 (manufactured by 3M Corporation), AsahiGuard (registered trademark) AG710 (manufactured by AGC Corporation), SURFION (registered trademark) S-382, SC101, SC102, SC103, SC104, SC105, SC106 (manufactured by AGC Seimi Chemical Co., Ltd.), etc. The content of these surfactants is preferably 0.01 to 2 parts by mass, more preferably 0.01 to 1 part by mass, based on 100 parts by mass of the side chain type polymer.
[0180] Specific examples of compounds that improve the adhesion between the phase difference material and the substrate include compounds containing functional silanes, and specific examples thereof include: 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 2-aminopropyltrimethoxysilane, 2-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, Ethoxysilane, N-3-triethoxysilylpropyl trivinyltetramine, N-3-trimethoxysilylpropyl trivinyltetramine, 10-trimethoxysilyl-1,4,7-triazadecane, 10-triethoxysilyl-1,4,7-triazadecane, 9-trimethoxysilyl-3,6-diazanonyl acetate, 9-triethoxysilyl-3,6-diazanonyl acetate, N-benzyl-3-aminopropyl trimethoxysilane, N-benzyl-3-aminopropyl triethoxysilane, N-phenyl-3-aminopropyl trimethoxysilane, N-phenyl-3-aminopropyl triethoxysilane, etc.
[0181] Furthermore, in order to improve the adhesion between the substrate and the phase difference material and prevent the degradation of characteristics due to backlight when constituting a polarizing plate, a phenoplast compound or an epoxy group-containing compound may be added to the polymer composition.
[0182] Specific examples of the phenolic plastic additive are shown below, but the invention is not limited thereto.
[0183] [Chemistry 23]
[0184]
[0185] Specific examples of the epoxy group-containing compound include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerol diglycidyl ether, dibromoneopentyl glycol diglycidyl ether, 1,3,5,6-tetraglycidyl-2,4-hexanediol, N,N,N′,N′-tetraglycidyl-m-xylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, and N,N,N′,N′-tetraglycidyl-4,4′-diaminodiphenylmethane.
[0186] When using a compound that improves adhesion to a substrate, the content is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the side chain polymer contained in the polymer composition. If the content is less than 0.1 parts by mass, the effect of improving adhesion cannot be expected, and if it is more than 30 parts by mass, the orientation of the liquid crystal may sometimes deteriorate.
[0187] As an additive, a photosensitizer can also be used. As the photosensitizer, a colorless sensitizer and a triplet sensitizer are preferred.
[0188] Examples of the photosensitizer include aromatic nitro compounds, coumarins (7-diethylamino-4-methylcoumarin, 7-hydroxy-4-methylcoumarin), ketocoumarins, carbonyl dicoumarins, aromatic 2-hydroxyketones, aromatic 2-hydroxyketones (2-hydroxybenzophenone, mono- or di-p-(dimethylamino)-2-hydroxybenzophenone, etc.), acetophenones, anthraquinones, xanthone, thioxanthone, benzanthrone, thiazolines (2-benzoylmethylene-3-methyl-β-naphthothiazoline, 2- (β-naphthoylmethylene)-3-methylbenzothiazoline, 2-(α-naphthoylmethylene)-3-methylbenzothiazoline, 2-(4-biphenylmethylene)-3-methylbenzothiazoline, 2-(β-naphthoylmethylene)-3-methyl-β-naphthothiazoline, 2-(4-biphenylmethylene)-3-methyl-β-naphthothiazoline, 2-(p-fluorobenzoylmethylene)-3-methyl-β-naphthothiazoline), oxazoline (2-benzoylmethylene) -3-methyl-β-naphthoxazoline, 2-(β-naphthoylmethylene)-3-methylbenzoxazoline, 2-(α-naphthoylmethylene)-3-methylbenzoxazoline, 2-(4-biphenylmethylene)-3-methylbenzoxazoline, 2-(β-naphthoylmethylene)-3-methyl-β-naphthoxazoline, 2-(4-biphenylmethylene)-3-methyl-β-naphthoxazoline, 2-(p-fluorobenzoylmethylene)-3-methyl-β-naphthoxazoline , etc.), benzothiazole, nitroaniline (m- or p-nitroaniline, 2,4,6-trinitroaniline, etc.), nitroacenaphthene (5-nitroacenaphthene, etc.), 2-[(m-hydroxy-p-methoxy)phenyl]benzothiazole, benzoin alkyl ether, N-alkylated phthaloyl ketone, acetophenone ketal (2,2-dimethoxyphenylacetophenone, etc.), naphthalene (2-naphthylmethanol, 2-naphthoic acid, etc.), anthracene (9-anthracenemethanol, 9-anthracenecarboxylic acid, etc.), benzopyran, azoindolizine, furanocoumarin (melokumarin), etc. Among these, aromatic 2-hydroxyketone (benzophenone), coumarin, ketocoumarin, carbonylbiscoumarin, acetophenone, anthraquinone, xanthone, thioxanthone and acetophenone ketal are preferred.
[0189] In the above-mentioned polymer composition, in addition to the above-mentioned substances, dielectrics and conductive substances may be added in order to change the electrical properties such as the dielectric constant and conductivity of the phase difference material, as long as the effects of the present invention are not impaired. In addition, cross-linking compounds may be added to increase the hardness and density of the film when the phase difference material is made.
[0190] The polymer composition is preferably prepared as a coating liquid in a manner suitable for forming a monolayer phase difference material. That is, the polymer composition used in the present invention is preferably prepared in the form of a solution, wherein the solution is a solution in which a side chain polymer and the solvent or compound for improving film thickness uniformity and surface smoothness, a compound for improving the adhesion between the liquid crystal alignment film and the substrate, etc. are dissolved in an organic solvent (good solvent).
[0191] Here, the content of the side chain type polymer in the composition is preferably 1 to 20% by mass, more preferably 3 to 20% by mass.
[0192] It should be noted that the polymer composition may contain other polymers in addition to the side chain polymer as long as the liquid crystal expression ability and photosensitivity are not impaired.
[0193] Examples of other polymers include polymers that are not photosensitive side chain polymers that can express liquid crystallinity, such as poly(meth)acrylate, polyamic acid, and polyimide.
[0194] The content of other polymers in the entire polymer component is preferably 0.5 to 80% by mass, more preferably 1 to 50% by mass.
[0195] [Step (II)]
[0196] In step (II), the coating film obtained in step (I) is irradiated with polarized ultraviolet light. When the film surface of the coating film is irradiated with polarized ultraviolet light, the substrate is irradiated with polarized ultraviolet light from a specific direction through a polarizing plate.
[0197] In the present invention, as the ultraviolet rays, as described above, ultraviolet rays in which the amount of light with a wavelength of 313 nm accounts for 10% or less of the total amount of light with a wavelength of 365 nm and light with a wavelength of 313 nm are used.
[0198] The amount of light with a wavelength of 313 nm in the polarized ultraviolet light used in the total amount of light with a wavelength of 365 nm and light with a wavelength of 313 nm is not particularly limited as long as it is 10% or less. From the viewpoint of further improving the phase difference value and birefringence of the obtained phase difference material, it is preferably 5% or less, more preferably 3% or less, and further preferably 1% or less. It is further preferred that the light with a wavelength of 313 nm is not substantially included. It should be noted that the term "not substantially included" refers to the polarized ultraviolet light after the light with a wavelength of 313 nm is cut off by a cutoff filter or the like.
[0199] As the ultraviolet rays, for example, light emitted from a high-pressure mercury lamp can be used.
[0200] The ratio of the wavelengths of polarized ultraviolet light can be adjusted by selecting the optimal wavelength ratio through filters, etc. For example, a bandpass filter (BPF) with 365nm as the center wavelength, or a long-wave pass filter (LWPF) that allows wavelengths longer than 313nm to pass, etc., can be used to reduce the light with a wavelength of 313nm.
[0201] The irradiation amount of polarized ultraviolet rays depends on the coating film used. That is, the irradiation amount is preferably set to be within the range of 1 to 70% of the amount of polarized ultraviolet rays that achieves the maximum value of ΔA, which is the difference between the ultraviolet absorbance in the direction parallel to the polarization direction of the polarized ultraviolet rays in the coating film and the ultraviolet absorbance in the direction perpendicular to the polarization direction of the polarized ultraviolet rays, and more preferably within the range of 1 to 50%.
[0202] [Step (III)]
[0203] The production method of the present invention may further include a step (III) of heating the coating film irradiated with polarized ultraviolet light in the step (II). The heating can impart an orientation control capability to the coating film.
[0204] As the heating means, a hot plate, a heat circulation type oven, an IR (infrared) type oven, or the like can be used.
[0205] The heating temperature can be determined in consideration of the temperature at which the coating film to be used exhibits liquid crystallinity, and is preferably within the temperature range at which the side chain polymer contained in the polymerizable composition to be used exhibits liquid crystallinity (hereinafter referred to as liquid crystal exhibiting temperature).
[0206] In the case of a film surface such as a coating, it is expected that the liquid crystal manifestation temperature of the coating surface is lower than the liquid crystal manifestation temperature when the side chain polymer is observed as a body. Therefore, the heating temperature is more preferably within the temperature range of the liquid crystal manifestation temperature of the coating surface. That is, for the temperature range of the heating temperature after polarized ultraviolet irradiation, it is preferred to use a temperature 10°C lower than the lower limit of the temperature range of the liquid crystal manifestation temperature of the side chain polymer as the lower limit and a temperature 10°C lower than the upper limit of the liquid crystal temperature range as the upper limit. If the heating temperature is lower than the above temperature range, there is a tendency that the anisotropic enhancement effect caused by heat in the coating becomes insufficient. In addition, if the heating temperature is too high compared to the above temperature range, there is a tendency that the state of the coating is close to an isotropic liquid state (isotropic phase), in which case it is sometimes difficult to reorient in one direction by self-organization.
[0207] It should be noted that the liquid crystal display temperature refers to a temperature above the liquid crystal transition temperature at which a phase transition occurs from a solid phase to a liquid crystal phase on the surface of a polymer or coating film and below the isotropic phase transition temperature (Tiso) at which a phase transition occurs from a liquid crystal phase to an isotropic phase. For example, the liquid crystal property is displayed below 130°C, which means that the liquid crystal transition temperature at which a phase transition occurs from a solid phase to a liquid crystal phase is below 130°C.
[0208] The thickness of the single-layer phase difference material produced by the manufacturing method of the present invention can be appropriately selected in consideration of the height difference, optical properties, and electrical properties of the substrate used, and is preferably 0.5 to 10 μm. However, in terms of the wavelength characteristics of the polarized ultraviolet light used in the present invention, the coating thickness during polarized ultraviolet light irradiation in step (II) is 0.5 μm or more, and in particular, a film thickness of 3.0 μm or more can also reach deep parts.
[0209] The single-layer retardation material obtained by the above-described production method has optical properties suitable for use in display devices, recording materials, and the like, and is particularly suitable as an optical compensation film such as a polarizing plate and a retardation plate for a liquid crystal display.
[0210] Example
[0211] Hereinafter, the present invention will be described in more detail with reference to Synthesis Examples, Production Examples, Examples, and Comparative Examples, but the present invention is not limited to the following Examples.
[0212] The following lists m1, m3, m4, m5, and m6 as monomers having a photoreactive group and m2 as a monomer having a liquid crystal group used in Examples.
[0213] m1 was synthesized according to the synthesis method described in International Publication No. 2011 / 084546. m2 and m3 were synthesized according to the synthesis method described in Japanese Patent Publication No. 9-118717. m4 was synthesized by the synthesis method described in Polymer, 52 (25), 5788-5794; 2011. m5 was synthesized by the synthesis method described in Macromolecules 2007, 40, 6355-6360. m6 was synthesized by the synthesis method described in non-patent literature (Macromolecules, 2002, 35, 706-713).
[0214] [Chemistry 24]
[0215]
[0216] In addition, the abbreviations of the reagents used in this example are shown below.
[0217] (Organic Solvent)
[0218] THF: Tetrahydrofuran
[0219] NMP: N-methyl-2-pyrrolidone
[0220] BC: Butyl Cellosolve
[0221] PGME: Propylene glycol monomethyl ether
[0222] PB: Propylene glycol monobutyl ether
[0223] (Polymerization initiator)
[0224] AIBN: 2,2′-azobisisobutyronitrile
[0225] (Surfactant)
[0226] R40: Megafac R-40 (manufactured by DIC Co., Ltd.)
[0227] (Silane coupling agent)
[0228] S-1: 3-Glycidoxypropyltriethoxysilane (LS-4668, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0229] [1] Synthesis of methacrylate polymer powder
[0230] [Synthesis example 1]
[0231] m1 (13.3 g, 0.04 mol) and m2 (18.4 g, 0.06 mol) were dissolved in THF (131.2 g), degassed with a diaphragm pump, and AIBN (0.49 g, 0.003 mol) was added and degassed again. Then, the mixture was reacted at 60° C. for 8 hours to obtain a methacrylate polymer solution. The polymer solution was added dropwise to methanol (1,000 mL), and the obtained precipitate was filtered. The precipitate was washed with methanol and dried under reduced pressure to obtain a methacrylate polymer powder P1.
[0232] [Synthesis Examples 2 to 5]
[0233] Methacrylate polymer powders P2 to P5 were obtained by the same procedure as in Synthesis Example 1 except that the monomers and polymerization solvents used were changed as shown in Table 1 below.
[0234] [Table 1]
[0235]
[0236] [2] Preparation of polymer solution
[0237] [Production Example 1-1]
[0238] Methacrylate polymer powder P1 (3 g) was added to NMP (7.5 g) and stirred at room temperature for 1 hour to dissolve. PB (1.5 g), PGME (1.5 g), BC (1.5 g), R40 (0.0015 g) and S-1 (0.03 g) were added to the solution and stirred to obtain a polymer solution T1. The polymer solution T1 was directly used as a phase difference material for forming a phase difference film.
[0239] [Production Example 1-2]
[0240] Methacrylate polymer powder P2 (3 g) was added to NMP (7.5 g) and stirred at room temperature for 1 hour to dissolve. PB (1.5 g), PGME (1.5 g), BC (1.5 g), R40 (0.0015 g) and S-1 (0.03 g) were added to the solution and stirred to obtain a polymer solution T2. The polymer solution T2 was directly used as a phase difference material for forming a phase difference film.
[0241] [Production Example 1-3]
[0242] Methacrylate polymer powder P3 (3 g) was added to NMP (7.5 g), and the mixture was stirred at room temperature for 1 hour to dissolve. PB (1.5 g), PGME (1.5 g), BC (1.5 g), R40 (0.0015 g) and S-1 (0.03 g) were added to the solution and stirred to obtain a polymer solution T3. The polymer solution T3 was directly used as a phase difference material for forming a phase difference film.
[0243] [Production Example 1-4]
[0244] Methacrylate polymer powder P4 (5.0 g) was added to NMP (18.1 g) and stirred at room temperature for 1 hour to dissolve. PB (3.3 g), PGME (3.3 g), BC (3.3 g) and R40 (0.0025 g) were added to the solution and stirred to obtain a polymer solution T4. The polymer solution T4 was directly used as a phase difference material for forming a phase difference film.
[0245] [Production Example 1-5]
[0246] Methacrylate polymer powder P5 (3 g) was added to NMP (7.5 g) and stirred at room temperature for 1 hour to dissolve. PB (1.5 g), PGME (1.5 g), BC (1.5 g), R40 (0.0015 g) and S-1 (0.03 g) were added to the solution and stirred to obtain a polymer solution T5. The polymer solution T5 was directly used as a phase difference material for forming a phase difference film.
[0247] [3] Fabrication of single-layer phase difference material
[0248] [Example 1-1]
[0249] The polymer solution T1 was filtered through a filter with a pore size of 5.0 μm, then spin-coated on an alkali-free glass substrate and dried on a hot plate at 60°C for 4 minutes to form a retardation film with a film thickness of 2.0 μm. Next, the retardation film was subjected to irradiation at 50, 100, 200, 400, 600, 800, and 1000 mJ / cm2 as shown in Table 3 through a polarizing plate. 2 The coating surface was irradiated with ultraviolet rays of 365 nm, and then heated in a heat circulation oven at 140° C. for 20 minutes to prepare a substrate S1 with a retardation film.
[0250] [Example 1-2]
[0251] A substrate S2 with a retardation film was prepared in the same manner as in Example 1-1, except that a 325 nm long wave pass filter (325LWPF) was used when irradiating with ultraviolet rays of 365 nm.
[0252] [Examples 1-3]
[0253] A substrate S3 with a retardation film was prepared in the same manner as in Example 1-2 except that T2 was used as the polymer solution.
[0254] [Examples 1-4]
[0255] A substrate S4 with a retardation film was prepared in the same manner as in Example 1-2 except that T3 was used as the polymer solution.
[0256] [Examples 1-5]
[0257] A substrate S5 with a retardation film was prepared in the same manner as in Example 1-1, except that a 365 nm band pass filter (365 nm BPF) was used when irradiating ultraviolet rays of 365 nm.
[0258] [Examples 1-6]
[0259] The polymer solution was filtered with a filter having a pore size of 5.0 μm using T4, and then spin-coated on a substrate and dried on a hot plate at 60°C for 4 minutes to form a retardation film having a film thickness of 1.5 μm. Next, the retardation film was subjected to irradiation at 50, 100, 200, 400, 800, and 1500 mJ / cm2 as shown in Table 4 through a polarizing plate. 2 The coating surface was irradiated with ultraviolet rays having a wavelength of 365 nm, and then heated in a heat circulation oven at 130° C. for 20 minutes to prepare a substrate S9 with a retardation film.
[0260] [Examples 1-7]
[0261] The polymer solution was filtered with a filter having a pore size of 5.0 μm using T5, and then spin-coated on a substrate and dried on a hot plate at 60°C for 4 minutes to form a retardation film having a film thickness of 2.0 μm. Next, 325LWPF was used through a polarizing plate at 250, 500, 1000, 2000, 4000, 8000, and 10000 mJ / cm 2 The coating surface was irradiated with ultraviolet rays having a wavelength of 365 nm, and then heated in a heat circulation oven at 160° C. for 20 minutes to prepare a substrate S11 with a retardation film.
[0262] [Comparative Example 1-1]
[0263] A substrate S6 with a retardation film was prepared in the same manner as in Example 1-1, except that the coating film surface was irradiated with ultraviolet rays having a wavelength of 313 nm through a polarizing plate.
[0264] [Comparative Example 1-2]
[0265] A substrate S7 with a retardation film was produced in the same manner as in Comparative Example 1-1 except that the polymer solution T2 was used.
[0266] [Comparative Examples 1-3]
[0267] A substrate S8 with a retardation film was produced in the same manner as in Comparative Example 1-1 except that the polymer solution T3 was used.
[0268] [Comparative Examples 1-4]
[0269] A substrate S10 with a retardation film was prepared in the same manner as in Example 1-6, except that the coating film surface was irradiated with ultraviolet rays having a wavelength of 313 nm through a polarizing plate.
[0270] [Comparative Examples 1-5]
[0271] A substrate S12 with a retardation film was prepared in the same manner as in Example 1-7, except that the coating surface was irradiated with ultraviolet rays having a wavelength of 313 nm through a polarizing plate without a cutoff filter.
[0272] Table 2 shows the summary of the above-mentioned embodiments and comparative examples.
[0273] In addition, the ratio of the light with a wavelength of 313 nm in the total irradiation amount was calculated|required by the following formula.
[0274] The ratio of light with a wavelength of 313 nm (%) = the radiation intensity at a wavelength of 313 nm / (the radiation intensity at a wavelength of 313 nm + the radiation intensity at a wavelength of 365 nm) * 100
[0275] [Table 2]
[0276]
[0277] The retardation value and Δn value of each of the substrates S1 to S12 produced in the above-mentioned examples and comparative examples were evaluated by the following method.
[0278] (1) Phase difference evaluation
[0279] The phase difference value at a wavelength of 550 nm was evaluated using AxoScan manufactured by Axometrics. Tables 3 to 5 show the results.
[0280] [Table 3]
[0281] Retardation Film Film thickness 50mJ 100mJ 200mJ 400mJ 600mJ 800mJ 1000mJ S1 2μm 53.2 74.4 116.8 147.6 151.5 142.4 134.3 S2 2μm 62.0 85.6 130.9 156.5 165.5 156.6 148.2 S3 2μm 72.2 81.8 107.9 135.0 144.1 150.6 153.7 S4 2μm 34.4 52.6 52.7 87.3 106.5 104.8 110.7 S5 2μm 57.5 83.4 119.7 149.1 162.0 164.8 163.6 S6 2μm 52.5 66.5 83.5 99.3 92.3 82.5 79.7 S7 2μm 101.1 107.0 106.8 92.7 85.4 80.1 78.7 S8 2μm 73.9 72.1 50.6 28.7 17.6 9.1 3.7
[0282] [Table 4]
[0283] Retardation Film Film thickness 50mJ 100mJ 200mJ 400mJ 800mJ 1500mJ S9 1.5μm 11.2 22.3 21.9 22.4 39.2 77.9 S10 1.5μm 21.5 24.3 30.4 37.3 28.7 1.4
[0284] [Table 5]
[0285] Retardation Film Film thickness 250mJ 500mJ 1000mJ 2000mJ 4000mJ 8000mJ 10000mJ S11 2μm 25.0 35.9 51.7 71.7 101.2 124.1 156.7 S12 2μm 62.7 84.6 90.2 105.7 64.2 21.2 1.4
[0286] (2) Δn value evaluation
[0287] The orientation degree (Δn) at a wavelength of 550 nm was calculated by dividing the value of (1) by the film thickness. Tables 6 to 8 show the results.
[0288] [Table 6]
[0289] Retardation Film Film thickness 50mJ 100mJ 200mJ 400mJ 600mJ 800mJ 1000mJ S1 2μm 0.027 0.037 0.058 0.074 0.076 0.071 0.067 S2 2μm 0.031 0.043 0.065 0.078 0.083 0.078 0.074 S3 2μm 0.036 0.041 0.054 0.068 0.072 0.075 0.077 S4 2μm 0.017 0.026 0.026 0.044 0.053 0.052 0.055 S5 2μm 0.029 0.042 0.060 0.075 0.081 0.082 0.082 S6 2μm 0.026 0.033 0.042 0.050 0.046 0.041 0.040 S7 2μm 0.051 0.053 0.053 0.046 0.043 0.040 0.039 S8 2μm 0.037 0.036 0.025 0.014 0.009 0.005 0.002
[0290] [Table 7]
[0291] Retardation Film Film thickness 50mJ 100mJ 200mJ 400mJ 800mJ 1500mJ S9 1.5μm 0.007 0.015 0.015 0.015 0.026 0.052 S10 1.5μm 0.014 0.016 0.020 0.025 0.019 0.001
[0292] [Table 8]
[0293] Retardation Film Film thickness 250mJ 500mJ 1000mJ 2000mJ 4000mJ 8000mJ 10000mJ S11 2μm 0.012 0.018 0.026 0.036 0.051 0.062 0.078 S12 2μm 0.031 0.042 0.045 0.053 0.032 0.011 0.001
Claims
1. A method for manufacturing a single-layer phase difference material, characterized in that: The process includes: (I) coating the polymer composition on a substrate and drying it to form a coating film; and (II) irradiating the coating film with polarized ultraviolet light, The polymer composition comprises a polymer having a photoreactive site in a side chain that undergoes photodimerization or photoisomerization with light of a wavelength of 365 nm, The photoreactive site is represented by the following formula (a3): ; In formula (a3), A 1 represents a single bond, -O-, -CH2-, -COO-, -OCO-, -CONH-, or -NH-CO-, L represents an alkylene group having 1 to 12 carbon atoms, wherein the hydrogen atoms of the alkylene group are independently substituted with halogen atoms or not, Y 1 represents a divalent benzene ring, Q 1 represents a group selected from a benzene ring and an alicyclic hydrocarbon ring having 5 to 8 carbon atoms, In Y 1 and Q 1 In the formula (a), the hydrogen atoms bonded to the benzene ring are each independently replaced by a cyano group, a halogen atom, an alkyl group having 1 to 5 carbon atoms, an alkylcarbonyl group having 1 to 5 carbon atoms, or an alkyloxy group having 1 to 5 carbon atoms, X 1 represents a single bond, -O-, -COO-, or -OCO-, n1 is 0, 1, or 2, When X 1 When the number is 2, X 1 Same or different from each other, When Q 1 When the number is 2, Q 1 The same or different from each other; the dotted line represents the bonding bond, The amount of light with a wavelength of 313 nm in the polarized ultraviolet light in the total amount of light with a wavelength of 365 nm and light with a wavelength of 313 nm is less than 10%, The thickness of the single-layer phase difference material is 0.5 to 10 μ m.
2. The method for manufacturing a single-layer phase difference material according to claim 1, wherein: The amount of the light having a wavelength of 313 nm in the total amount of the light having a wavelength of 365 nm and the light having a wavelength of 313 nm is 5% or less.
3. The method for manufacturing a single-layer phase difference material according to claim 1, wherein: The polarized ultraviolet light does not include light with a wavelength of 313 nm.
4. The method for manufacturing a single-layer phase difference material according to claim 1, wherein: The manufacturing method of the single-layer phase difference material comprises the following steps: (III) Heating the coating film irradiated with the polarized ultraviolet rays.
5. The method for manufacturing a single-layer phase difference material according to claim 1, wherein: The polymer also has a side chain that does not show photo-orientation.
6. The method for manufacturing a single-layer phase difference material according to claim 5, wherein: The side chain that does not exhibit photo-alignment is any one of the side chains selected from the following formulae (1) to (12): ; ; In formulas (1) to (12), A 3 and A 4 each independently represents a single bond, -O-, -CH2-, -C(=O)-O-, -OC(=O)-, -C(=O)NH-, or -NHC(=O)-, R 11 represents -NO2, -CN, a halogen atom, a phenyl group, a naphthyl group, a biphenyl group, a furyl group, a monovalent nitrogen-containing heterocyclic group, a monovalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, an alkyl group having 1 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms, and R 12 represents a group selected from phenyl, naphthyl, biphenyl, furyl, a monovalent nitrogen-containing heterocyclic group, a monovalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, and a group obtained by combining them, wherein the hydrogen atom bonded to them is or is not replaced by -NO2, -CN, a halogen atom, an alkyl group having 1 to 5 carbon atoms, or an alkoxy group having 1 to 5 carbon atoms, and R 13 represents a hydrogen atom, -NO2, -CN, -CH=C(CN)2, -CH=CH-CN, a halogen atom, a phenyl group, a naphthyl group, a biphenyl group, a furyl group, a monovalent nitrogen-containing heterocyclic group, a monovalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, an alkyl group having 1 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms, E represents -C(=O)O- or -OC(=O)-, d represents an integer of 1 to 12, k1 to k5 are each independently an integer of 0 to 2, the total of k1 to k5 is 2 or more, k6 and k7 are each independently an integer of 0 to 2, the total of k6 and k7 is 1 or more, m1, m2 and m3 are each independently an integer of 1 to 3, n is 0 or 1, Z 1 and Z 2 Each independently represents a single bond, -C(=O)-, -CH2O- or -CF2-, and the dotted line represents a bond.
7. The method for producing a single-layer phase difference material according to claim 5 or 6, wherein: The side chain having a photoreactive site is a group represented by the following formula (a3-1): ; In the formula, L, Y 1 and dotted lines have the same meanings as above.
Citation Information
Patent Citations
Optical component, orientation layer, and layerable polymerisable mixture
EP1090325A1
Preparation of orientated film
JP1987070407A
Cross-linkable optically active polymer material
JP1997118717A
Production of optical isomer
JP1997208957A
Birefringent film and its production
JP1999189665A